Abstracts and Keywords - Weerheijm, Ron; Kornet, Amber; Beuken, Juliëtte A.; Mittendorff, Kariene; Pouwels, Jan; Emmers, Elke; Verschuren, Pieter; van Genugten, Klaartje (Tijdschrift voor Hoger Onderwijs, 2023)
De abstracts en keywords van de artikelen van de auteurs in TvHO 2023 (41) nr. 4